Early marriage as a risk factor for undernutrition among children aged under three years old in Gangga Subdistrict, North Lombok District - Suhartiningsih; Ni Luh Putu Suariyani; Mangku Karmaya (Universitas Udayana, 2018)
Background and purpose: The prevalence of severe and mild undernutrition among children aged under five years in North Lombok District is ranked second in West Nusa Tenggara Province after Bima City. The number of reported cases of early marriages in West Nusa Tenggara is higher than the national average. This study aims to examine the association between early marriages and undernutrition among children aged under three years in Gangga Subdistrict, North Lombok District. Methods: A case-control study was conducted with a total of 49 cases (severe undernourished children) and 98 controls (normalweight children). A systematic random sampling was used to select all cases and controls from the health post register based on the weight/age indicator in Gangga Public Health Centre. Variables of sex and residency were matched between cases and controls. Data were collected from October to November 2016 through interviews with the mother at their house. Logistic regression using a software STATA SE 12.1 was employed to identify the association between early marriages and nutritional status of the children. Results: Cases and controls were comparable based on children’s gender, mother’s age, area of residency, employment status of mother, and family income. There were significant differences on children’s age and mother’s education. Multivariate analysis showed an association between the nutritional status and early marriages with adjusted odds ratio (AOR)=5.21 (95%CI: 1.36-19.95), the frequency of sickness over the last three months (AOR=1.93; 95%CI: 1.26-2.97) and low birth weight (AOR=14.12; 95%CI: 3.37-59.05). Conclusions: Early marriages, frequency of sickness over the last three months, and low birth weight are associated with undernutrition among children aged under three years. Preventative measures to prevent early marriages, child infections and low birth weight need to be enhanced.